Masseter muscle pressure injury: First report of a prone position complication in patients with COVID-19. (August 2022) - Rohée-Traoré, Adèle; Kün-Darbois, Jean-Daniel; Boucher, Sophie
Abstract: We report the case of a 59-year-old, obese woman who underwent prolonged prone position during the medical management of an acute respiratory distress syndrome induced by SARS-CoV-2 infection, complicated by a masseter muscle pressure injury. Such side effect may be underestimate in intensive care units and should be prevent by prophylactic dressings on facial weight-bearing sites. The understanding of facial deep tissue injury is essential to guide clinical detection and management of such a complication in COVID-19 patients.